ANALYSIS OF PETROLEUM FRACTIONS OF KARAULBAZAR (Scientific journal of the Fergana State University, 2023)
Aim of the article consists of studying the composition of natural petroleum acids isolated from petroleum oils, commercial oil, oilfield effluents, as well as synthetic acids obtained by the oxidation of naphthenic concentrates and diesel fuel fractions, determining naphthenic acids in oil and petroleum products in Karaulbazar. The experiments showed the yield of the fractions. A method has been developed for determining the amount of naphthenic acids in soap naphthene by three methods of black titration using double indicators of alkali waste, as well as the composition of isoparaffin-naphthenic hydrocarbons obtained by the reduction of naphthenic acids from Karaulbozor oil, and the fractional composition of oil acids isolated from Karaulbozor oil.